Net Radiation During Clear Weather in the Snow-Free Season for Various Types of Surfaces, Poste-de-la-Baleine (Great Whale), Québec - Wilson, Cynthia (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1975)
During the snow-free seasons 1972-1975, point fluxes of net radiation (Q*) and incoming solar radiation (K↓) were measured in clear weather for different surfaces near Poste-de-la-Baleine (Great Whale), Québec. The relationship between Q* and K↓ is described for each type of surface in terms of the simple ratio Q*/K↓. 100% and the linear egression curve, to enable estimates of net radiation to be made from the more available measured or calculated K↓.The results suggest that the use of portable instruments for relatively short periods of carefully controlled field observations offers an inexpensive method of predicting net radiation in the less accessible north, if the measurements are stratified according to weather and surface conditions. A comparison of the regression curves permits a simple quantitative estimate of the potential differences in the net energy at the surface, resulting from projected changes to the terrain with northern development. The curves in this present article refer to clear weather. Although it is relatively rare on this coast, it is believed to have an importance in the energy climate and ecology quite beyond its limited frequency.